2015
DOI: 10.1148/radiol.14140524
|View full text |Cite
|
Sign up to set email alerts
|

How Accurate Is Multiparametric MR Imaging in Evaluation of Prostate Cancer Volume?

Abstract: Vh can be estimated by using Vmax in aggressive tumors or in tumors with high Likert scores.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
52
1
2

Year Published

2015
2015
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 77 publications
(63 citation statements)
references
References 55 publications
6
52
1
2
Order By: Relevance
“…The current standard for prostate MRI dictates a multiparametric approach with combines these anatomic sequences with functional techniques such as diffusion-weighted (DW) and dynamic contrast-enhanced (DCE) MRI. While the benefits of this multiparametric approach for PCA detection and staging have been widely reported [2226], the complexity of the imaging interpretation has also increased. Until recently prostate MRI was interpreted using loosely defined criteria through qualitative “Likert” suspicion scores, however guidelines aiming to standardize prostate MRI acquisition and interpretation have now been published, including the Prostate Imaging Reporting and data system (PI-RADS), with an updated PI-RADS version 2 recently released [2729].…”
Section: Introductionmentioning
confidence: 99%
“…The current standard for prostate MRI dictates a multiparametric approach with combines these anatomic sequences with functional techniques such as diffusion-weighted (DW) and dynamic contrast-enhanced (DCE) MRI. While the benefits of this multiparametric approach for PCA detection and staging have been widely reported [2226], the complexity of the imaging interpretation has also increased. Until recently prostate MRI was interpreted using loosely defined criteria through qualitative “Likert” suspicion scores, however guidelines aiming to standardize prostate MRI acquisition and interpretation have now been published, including the Prostate Imaging Reporting and data system (PI-RADS), with an updated PI-RADS version 2 recently released [2729].…”
Section: Introductionmentioning
confidence: 99%
“…All patients gave written informed consent. The database was used for other studies evaluating prostate cancer detection rates [3] and accuracy of tumor volume estimation [31] at multiparametric MR imaging, existing MR scoring systems [11] and diagnostic accuracy of quantitative MR parameters [3234]. These studies do not overlap with the present one that aims at understanding the relative weight of non-quantitative sequence-specific findings in the characterization of aggressive prostate cancers, in order to improve current MR scoring systems.…”
Section: Methodsmentioning
confidence: 99%
“…Thus far, few studies have focused on tumor volume estimation (343536). In 2002, the value of MR spectroscopic imaging in measuring tumor volume in nodules > 0.5 cm3 was assessed and researchers showed that it was positively correlated with histopathologic tumor volume with a Pearson correlation coefficient of 0.59 (37).…”
Section: Mri Detection Of Clinically Significant Diseasementioning
confidence: 99%